PERANCANGAN APLIKASI PEMBELAJARAN DENGAN KONSEP GAMIFIKASI : Systematic Literature Review - Erba Lutfina; Robby O. Cahyadi Setiawan; Ahmad Nugroho; M. Zakki Abdillah (Universitas Methodist Indonesia, 2023)
The concept of gamification has been considered as one of the innovative methods in learning to increase student motivation and learning outcomes. In this study, researchers analyzed the application of the gamification concept by using a systematic literature review method. Researchers collected several journals about the application of gamification in learning and analyzed the results of these journals. The purpose of this study is to compare which method is best used in applying the concept of gamification in learning